2017
DOI: 10.1016/j.jclinepi.2017.01.014
|View full text |Cite
|
Sign up to set email alerts
|

GRADE equity guidelines 1: considering health equity in GRADE guideline development: introduction and rationale

Abstract: ObjectivesThis article introduces the rationale and methods for explicitly considering health equity in the Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology for development of clinical, public health, and health system guidelines.Study Design and SettingWe searched for guideline methodology articles, conceptual articles about health equity, and examples of guidelines that considered health equity explicitly. We held three meetings with GRADE Working Group members and invite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 38 publications
0
77
0
2
Order By: Relevance
“…We also reviewed non-randomized studies that analyzed other socio-economic and cultural aspect that could have an impact on equity. We extracted data on the influence of several factors (i.e age, disability, sexual orientation, time-dependent situations, relationships, place of residence, race/ethnicity/culture, language, occupation, gender/sex, religion, education, socioeconomic status, or social capital) on the absolute effectiveness of PUFAs or the importance of the problem [33,34]. We extracted both quantitative and qualitative data.…”
Section: Equitymentioning
confidence: 99%
See 1 more Smart Citation
“…We also reviewed non-randomized studies that analyzed other socio-economic and cultural aspect that could have an impact on equity. We extracted data on the influence of several factors (i.e age, disability, sexual orientation, time-dependent situations, relationships, place of residence, race/ethnicity/culture, language, occupation, gender/sex, religion, education, socioeconomic status, or social capital) on the absolute effectiveness of PUFAs or the importance of the problem [33,34]. We extracted both quantitative and qualitative data.…”
Section: Equitymentioning
confidence: 99%
“…Watters et al [50] identified supplements as the cheapest way, immediately after fish liver oil, to take a high dosage (≥500 mg/day) of PUFAs such as DHA and EPA. The estimated cost of the equivalent of a tablet containing 1000 mg of EPA plus DHA was $0.88 ± $0.16 in the USA [33]. Similarly, according to another USA study, which considered a wider range of marketed PUFAs' supplements, the estimated cost of the equivalent of a tablet containing 1000 mg EPA plus DHA was $0.70 ± $1.11 [51].…”
Section: Resources Requiredmentioning
confidence: 99%
“…Incorporating equity into guideline development necessitates modifying the methodology accordingly . This is evidenced by revisions in the second edition of the WHO Handbook for Guideline Development, which has added a new chapter on equity and other social determinants of health; and in the evolving GRADE framework that has recently launched a series that gives detailed guidance on health equity considerations in guideline development …”
Section: Discussionmentioning
confidence: 99%
“…21 This is evidenced by revisions in the second edition of the WHO Handbook for Guideline Development, which has added a new chapter on equity and other social determinants of health; and in the evolving GRADE framework that has recently launched a series that gives detailed guidance on health equity considerations in guideline development. 22,23 The method of collecting CPGs employed was designed using the lens of a health care practitioner attempting to attain CPGs for his/her personal use. We were initially limited by what could be freely accessed online or from office libraries.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of the evidence and the confidence in the estimate of the effect across outcomes were assessed utilizing the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. 28,29 Accordingly, data from randomized-controlled trials are considered high-quality evidence, but the quality can be rated down due to risk of bias, imprecision, indirectness, imprecision, and publication bias. 29…”
Section: Study Appraisalmentioning
confidence: 99%